The miniJPAS survey - Galaxy populations in the most massive cluster in miniJPAS: mJPC2470-1771 - Rodríguez-Martín, Julio E.; Delgado, R. M. González; Martínez-Solaeche, G.; Díaz-García, L. A.; Amorim, A. de; García-Benito, R.; Pérez, E.; Fernandes, R. Cid; Carrasco, E. R.; Maturi, Matteo; Finoguenov, A.; Lopes, P. a. A.; et al. (Astronomy and astrophysics, 2022)
The Javalambre-Physics of the Accelerating Universe Astrophysical Survey (J-PAS) is a photometric survey that is poised to scan several thousands of square degrees of the sky. It will use 54 narrow-band filters, combining the benefits of low-resolution spectra and photometry. Its offshoot, miniJPAS, is a 1 deg 2 survey that uses J-PAS filter system with the Pathfinder camera. In this work, we study mJPC2470-1771, the most massive cluster detected in miniJPAS. We survey the stellar population properties of the members, their star formation rates (SFR), star formation histories (SFH), the emission line galaxy (ELG) population, spatial distribution of these properties, and the ensuing effects of the environment. This work shows the power of J-PAS to study the role of environment in galaxy evolution. We used a spectral energy distribution (SED) fitting code to derive the stellar population properties of the galaxy members: stellar mass, extinction, metallicity, (u − r) res and (u − r) int colours, mass-weighted age, the SFH that is parametrised by a delayed-τ model (τ, t 0), and SFRs. We used artificial neural networks for the identification of the ELG population via the detection of the H α, [NII], H β, and [OIII] nebular emission. We used the Ew(H α)-[NII] (WHAN) and [OIII]/H α-[NII]/H α (BPT) diagrams to separate them into individual star-forming galaxies and AGNs. We find that the fraction of red galaxies increases with the cluster-centric radius; and at 0.5 R 200 the red and blue fractions are both equal. The redder, more metallic, and more massive galaxies tend to be inside the central part of the cluster, whereas blue, less metallic, and less massive galaxies are mainly located outside of the inner 0.5 R 200. We selected 49 ELG, with 65.3% of them likely to be star-forming galaxies, dominated by blue galaxies, and 24% likely to have an AGN (Seyfert or LINER galaxies). The rest are difficult to classify and are most likely composite galaxies. These latter galaxies are red, and their abundance decreases with the cluster-centric radius; in contrast, the fraction of star-forming galaxies increases outwards up toR 200. Our results are compatible with an scenario in which galaxy members were formed roughly at the same epoch, but blue galaxies have had more recent star formation episodes, and they are quenching out from within the cluster centre. The spatial distribution of red galaxies and their properties suggest that they were quenched prior to the cluster accretion or an earlier cluster accretion epoch. AGN feedback or mass might also stand as an obstacle in the quenching of these galaxies.
Gesehen am 01.02.2023